Selection and Application of DC Support Capacitor in Power Converter - TANG Haiyan; TANG Zhou (Kongzhi Yu Xinxi Jishu)
It introduces the advantages and disadvantages of electrolytic capacitor and metalized film capacitor in various circuit topologies of power converters, describes application notices of the capacitor in detail and presents the specific design parameters in a variety of circuit topologies. Calculated parameters show that metalized film capacitor is the better choice and can be used widely in power converters especially high-voltage DC input products.